2015
DOI: 10.1371/journal.pone.0142876
|View full text |Cite
|
Sign up to set email alerts
|

Early Assessment of Colorectal Cancer Patients with Liver Metastases Treated with Antiangiogenic Drugs: The Role of Intravoxel Incoherent Motion in Diffusion-Weighted Imaging

Abstract: PurposeTo assess the feasibility and effectiveness of quantitative intravoxel incoherent motion (IVIM) of Diffusion-weighted imaging (DWI) in the assessment of liver metastases treated with targeted chemotherapy agents.Methods12 patients with unresectable liver metastases from colorectal cancer were enrolled and received neoadjuvant FOLFIRI (5-fluorouracil, leucovorin, irinotecan) plus bevacizumab therapy. DWI was performed for 36 metastases at baseline and after 14 days from starting the treatment. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 28 publications
4
85
0
Order By: Relevance
“…The results of increased D ′ and decreased f ′ in responders are in agreement with increased D and decreased f and D * in histologically confirmed coagulation necrosis area of rabbit VX2 tumors after radiofrequency ablation 39. In a recent study, the early response of liver metastases from colorectal cancer to a combined therapy of antiangiogenic plus cytotoxic agents (FOLFIRI plus bevacizumab) was assessed 40. Responders showed unchanged D and D * values, but decreased f values as a sign of reduced microvessel density.…”
Section: Discussionsupporting
confidence: 55%
“…The results of increased D ′ and decreased f ′ in responders are in agreement with increased D and decreased f and D * in histologically confirmed coagulation necrosis area of rabbit VX2 tumors after radiofrequency ablation 39. In a recent study, the early response of liver metastases from colorectal cancer to a combined therapy of antiangiogenic plus cytotoxic agents (FOLFIRI plus bevacizumab) was assessed 40. Responders showed unchanged D and D * values, but decreased f values as a sign of reduced microvessel density.…”
Section: Discussionsupporting
confidence: 55%
“…Examples include Îą-difluoromethylornithine (DFMO; trypanosomiasis/African sleeping sickness) 26 and 5-fluorouracil (cancer chemotherapy). 27 That said, outfitting AAs with the Îą-(1′-fluoro)vinyl functionality in place of the Îą-proton has not been possible heretofore. This would be required if one wished to deploy this trigger in the active sites of PLP-dependent amino acid decarboxylase (AADC) or retroaldolase enzymes, for example.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional mono‐exponential analysis model, which estimates apparent diffusion coefficient (ADC) as an index of overall water movement, IVIM imaging has the advantage of providing a better explanation of the actual DW signal and separate evaluation of diffusion and perfusion changes in tissues . Several prior studies have demonstrated the potential value of IVIM parameters as meaningful imaging biomarkers for assessing various pathological conditions in the abdominal organs and for monitoring therapeutic responses in oncology patients …”
mentioning
confidence: 99%